The Fourth Industrial Revolution (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article describes the essence of the fourth industrial revolution, its technological foundations and its impact on industrial production processes . The fourth industrial revolution is modern technologies, including cloud computing , artificial intelligence, robotics based on automation and optimization of production. The article analyzes the main advantages of the fourth industrial revolution, such as increasing the efficiency of industrial production, ensuring flexibility and reducing costs . Staffing shortages, cyber security and investment issues related to the transition to new technologies are also addressed. The influence of the fourth industrial revolution on the world economy, in particular, how much it affected the development of the economy of Uzbekistan is considered.